COMPREHENSIVE META-ANALYSIS OF CONGENITAL UMBILICAL HERNIA AND ITS SURGICAL MANAGEMENT IN PEDIATRIC PATIENTS - Muhammad Fayyaz; Iqra Javed; Kamran Ahmed; Saleem Ahmed Bhutto; Muhammad Muneeb Ather; Ghasaq Al Obaidi; Muhammad Haris (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Congenital umbilical hernia is a common pediatric condition caused by incomplete closure of the umbilical ring, often resolving spontaneously within the first few years of life. However, persistent hernias beyond 4–5 years require surgical intervention. The choice between open and laparoscopic repair, as well as the role of mesh reinforcement, remains debated concerning recurrence rates and postoperative complications. This meta-analysis comprehensively evaluates the efficacy and safety of different surgical approaches for congenital umbilical hernia in pediatric patients.Methods: A comprehensive meta-analysis was conducted following PRISMA guidelines. A systematic search was performed in PubMed, Google Scholar, Scopus, Web of Science, and Cochrane Library for studies published between January 2019 and September 2024. Randomized controlled trials (RCTs), cohort studies, and case-control studies comparing open and laparoscopic umbilical hernia repair in pediatric patients were included. Data extraction and quality assessment were conducted independently by two reviewers. Meta-analysis was performed using Review Manager (RevMan) software, and pooled estimates were calculated for recurrence rates, postoperative complications, operative time, and hospital stay. Heterogeneity was assessed using the I² statistic, and publication bias was evaluated using funnel plots and Egger’s test.Results: A total of 45 studies involving 12,483 pediatric patients were included. The analysis showed no significant difference in recurrence rates between open and laparoscopic repair (RR: 1.08, 95% CI: 0.85–1.38, I² = 43%). However, laparoscopic repair with mesh demonstrated significantly lower recurrence rates (RR: 0.57, 95% CI: 0.36–0.89, I² = 58%). Mesh placement was associated with increased postoperative complications (RR: 1.45, 95% CI: 1.10–1.90, I² = 65%). Laparoscopic repair resulted in longer operative time (MD: 12.5 min, 95% CI: 8.4–16.6, I² = 72%) but significantly shorter hospital stays (MD: -1.4 days, 95% CI: -2.1 to -0.8, I² = 33%).Conclusion: Both open and laparoscopic approaches are effective for umbilical hernia repair in pediatric patients. While mesh use reduces recurrence rates, it increases postoperative complications. Laparoscopic repair offers shorter hospital stays but requires specialized expertise. Individualized decision-making based on hernia size, patient characteristics, and institutional resources is essential for optimizing surgical outcomes. Further high-quality RCTs are needed to establish standardized guidelines for pediatric umbilical hernia repair.